MODEL ANTISIPASI KONFLIK PEMILUKADA BERBASIS PARTISIPASI MASYARAKAT DI JAWA TENGAH ( Studi di Kabupaten Kebumen, Kabupaten Rembang, Kota Semarang, dan Kota Pekalongan ) - Nurul Akhmad; Iqbal Wibisono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Regional leader general election conflict potential anticipation model research based on this society participation is : (1) At surface overshadows by conflict existence many involve society ; (2) Still the low society participation in join in to do anticipation towards potential regional leader general election conflict ; (3) Necessary looked for regional leader general election conflict potential anticipation model based on society participation. This research is a case study that are : (1) Kebumen Regency; (2) Rembang Regency; (3) Semarang City; (4) Pekalongan City. Two manners to get data that is (1) observation and (2) interview deepens, the validity process by using method triangulatings, so that truth and well guaranted data quality. This research aim is that is to detects: (1) How far society participation has been done in join in to do conflict anticipation in regional leader general election; (2) to detect potential regional leader general election conflict; (3) regional leader general election conflict potential area; (4) conflict potential heavy in every conflict area; (5) To find the anticipation model based on society participation. This research benefit is that is : (1) According to teoretik, can be embryo for theory reconstruction efforts about regional leader general election conflict anticipation based on society participation (2) According to practise, from this watchfulness result can be new reference for all regional leader general election the interested parties (Local Government, Regency/City General Election Commitee, Election Supervisor Commitee, TNI/Police, Society, and Private Side) in the efforts realizes democratic regional leader general election, have a certain quality, and safe; (3) Detectable a regional leader general election conflict potential anticipation model based on society participation. This research result shows (1) to decreased it society participation, (2) potential regional leader general election conflict; (3) still the hoisterous of money policies, (4) denial existence towards regional leader general election result by candidate pair that lose, (5) all regional leader general election quarrel accusations that submitted by pair that lose to aversed constitution court of justice; (6) found a regional leader general election conflict potential anticipation model based on society participation. Conclusion that can be taken from this research that is (1) decreased it society participation in regional leader general election be caused satisfied taste factor follow regional leader general election, technical obstacle, attitude apreori society, (2) the hoisterous of money policies because weak the law rule; (3) denial towards chosen candidate pair by candidate pair that loses because democracy culture unfavourable.